IMPLEMENTASI BACA, GAMBAR, CERITA SEBAGAI UPAYA PENINGKATAN LITERASI LITERASI SISWA KELAS III SDN 1 SANDIK - Nurannisa Ramadhani; Siti Hawa; Herly Yuniarti; Rismi; Aurelia Salsabila; Alfina Dwijayanti; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low interest in reading and the difficulty in understanding texts among elementary school students remain serious challenges that affect overall learning success. This study aims to describe and analyze the implementation of the Read, Draw, Tell" method as an effort to improve the literacy of third-grade students at SDN 1 Sandik. Through a 15-minute literacy program before classes began, students facilitated habituation activities in a relaxed and enjoyable atmosphere. The research methodology focuses on analyzing the program's implementation process, from the planning stage of selecting relevant stories to field practice. The results indicated that prior to the intervention, students' literacy skills were highly varied and tended to be suboptimal, particularly in processing meaning and expressing ideas. However, after the implementation of this method, significant positive changes were observed. The use of drawing media helped students visualize story arcs concretely, while the activity of retelling their work improved their courage and verbal communication skills. Despite obstacles such as limited time and differences in learning speeds among students, support from facilitators and an interactive learning atmosphere were key supporting factors for the program's success. Overall, the "Read, Draw, Tell" method proved effective in increasing student engagement and learning motivation, making it a viable alternative strategy for strengthening literacy in elementary schools.